Strategi Social Media Marketing “Nikahmu Wedding Organizer” Dalam Meningkatkan Brand Awareness Melalui Instagram Pasca Pandemi Covid-19 - Nabila, Talitha; Suksmawati, Herlina (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
One of the sectors that had stopped due to the Covid-19 pandemic was the wedding organizer service sector. Nikahmu Wedding Organizers are starting to rebuild their name by developing a post-Covid-19 social media marketing strategy through their Instagram account @nikahmuweddingorganizer. This research was conducted with the aim of finding out how the social media strategy carried out by Nikahmu Wedding Organizer through Instagram after being hit by the Covid-19 pandemic used a qualitative descriptive method. Researchers use descriptive qualitative because the method is intended and can be used to gain an understanding of the meaning of human problems and social phenomena. Nikahmu Wedding Organizer uses Instagram as a platform for social media marketing through the account @nikahmuweddingorganizer. The Instagram account @nikahmuweddingorganizer utilizes Instagram's features for marketing and increasing brand awareness. The features used include feeds, reels, highlights, and stories. Nikahmu Wedding Organizer in its Instagram also implements four of the five promotional mixes, namely advertising through Instagram Ads, uploading sales promotions, conducting public relations and publication activities, and direct marketing through Instagram. Nikahmu Wedding Organizer does not make personal sales through its Instagram account because it is considered less effective if it is done online. Keywords: Social Media Marketing, promotion mix and Brand Awareness